(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Cultural issues in translation involve challenges with culture-specific terms, idioms, social norms, humor, symbols, and values. Effective translation requires cultural understanding and strategies like adaptation or explanation to preserve meaning across languages.